2016
DOI: 10.4315/0362-028x.jfp-15-274
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Salmonella Serotypes Isolated from Fresh Produce Marketed in the United States

Abstract: Salmonella continues to rank as one of the most costly foodborne pathogens, and more illnesses are now associated with the consumption of fresh produce. The U.S. Department of Agriculture Microbiological Data Program (MDP) sampled select commodities of fresh fruit and vegetables and tested them for Salmonella, pathogenic Escherichia coli, and Listeria. The Salmonella strains isolated were further characterized by serotype, antimicrobial resistance, and pulsed-field gel electrophoresis profile. This article sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…However, they have both caused salmonellosis outbreaks, associated with alfalfa sprouts and chia seeds, respectively (12,14). Moreover, S. Cubana was the serovar most frequently recovered from sprout samples collected by the U.S. Department of Agri- culture Microbiological Data Program (MDP) between 2002 and 2012 (27). As shown in previous studies, initial inoculation levels played a significant role in the growth of Salmonella on sprouts.…”
Section: Discussionmentioning
confidence: 80%
“…However, they have both caused salmonellosis outbreaks, associated with alfalfa sprouts and chia seeds, respectively (12,14). Moreover, S. Cubana was the serovar most frequently recovered from sprout samples collected by the U.S. Department of Agri- culture Microbiological Data Program (MDP) between 2002 and 2012 (27). As shown in previous studies, initial inoculation levels played a significant role in the growth of Salmonella on sprouts.…”
Section: Discussionmentioning
confidence: 80%
“…Italian pasta was reported as one of the sources of S. arizonae infection in the United Kingdom (9). Even in the modern era, S. arizonae has been identified in fresh vegetables, pork and traditional Italian cheeses (10)(11)(12). One epidemiological study conducted in Japan showed that several Salmonella sp., including S. arizonae, were isolated from 12.3% (7 out of 57 specimens) of chicken meat samples sold by domestic supermarkets, and S. arizonae was isolated from 1 of these 7 products (13).…”
Section: Discussionmentioning
confidence: 99%
“…These results could be explained by dose-response effects. For example, the level of Salmonella contamination of raw produce, when detected, is often very low [17]. This could translate into lower doses for cases exposed to contaminated produce and lower doses can result in longer incubation periods [8].…”
Section: Epidemiology and Infection 427mentioning
confidence: 99%